Factors influencing self-awareness with blood glucose level among patients with type 2 diabetes - Carles, Carles; Girsang, Ermi; Nasution, Ali Napiah (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Type 2 diabetes mellitus is a global health problem with increasing prevalence, especially in urban areas. Management of the disease requires patient self-awareness of factors such as physical activity, balanced diet, stress control, and medication adherence. Purpose: To analyze the influence of physical activity, balanced diet, stress control, and medication adherence on patients' self-awareness behavior in controlling blood sugar levels in urban communities of Riau Province. Method: Quantitative research with a cross-sectional design involved 105 respondents aged 40-65 years who were registered as type 2 DM patients at a health center in an urban area of Riau Province. Data were collected using a questionnaire and analyzed using the chi-square test and odds ratio. Results: Insufficient physical activity increased the risk of low patient self-awareness by 2.8 times (p=0.016). Unbalanced diet increased the risk by 3.5 times (p=0.004). Poor stress control increased the risk by 4.5 times (p=0.0001). Meanwhile, lack of medication adherence increased the risk by 3.2 times (p=0.007). Conclusion: Physical activity, balanced diet, stress control, and medication adherence significantly influenced patients' self-awareness in diabetes management. Community-based interventions are needed to improve the management of this disease.